Cytotoxicity effect of Zataria multiflora Boiss. on two human colon carcinoma cell lines - F. Sharififar; M. Miri-Moghaddam; S.N. Nematollahi-Mahani; H. Forootanfar; M. Asgharian Rezee (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Natural products are one of the major sources for investigations of novel medicines. Zataria multiflora Boiss (ZM) has shown pharmacological activities especially in gastrointestinal tract; however, there are limited studies about its cytotoxicity effects. In this study, the effect of Zataria multiflora was examined on two colon cancer cell lines (SW-48 and HT-29). Methods: Hydro-alcoholic extract of ZM and its fractions including chloroform, petroleum ether and methanol extract were prepared by warm maceration method. Different concentrations were prepared and examined on SW-48 and HT-29 cell lines using 2-(4, 5-dimethylthiazol-2-yl) 2, 5-diphenyltetrazolium bromide (MTT) assay. Results: The results of the present study have shown the cytotoxic effect of some fractions of ZM. The most considerable cytotoxic effect was shown against HT-29 cell line. Also, total ZM extract and the petroleum ether fraction demonstrated cytotoxic effects with IC50 values of 44.22 and 33.42 µg/ml on SW-48 and HT-29 cell lines, respectively. Conclusion: Zataria multiflora was cytotoxic to against colon cancer cell lines HT-29 and SW-48.